POTENTIAL SOURCE OF FRESH AND PHOTOACTIVATED GOMUTRA FOR STUDY OF ANTIOXIDANT AND ANTIPATHOGENIC ACTIVITIES AGAINST VARIOUS PATHOGENS - Praba.s, Lakshmi; GNANASARASWATHI. M,; RAJADURAI JESUDOSS.R.P,; RAMYA. N,; NANDHINI DEVI. S, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Nowadays, the increase in use of antimicrobial drugs has been attributed to indiscriminate use of broad-spectrum antibiotics, immunosuppressive agents and ongoing epidemics of HIV infection. These drugs are economically too expensive and inadequate for the treatment of diseases in developing countries, and it also has some serious side effects. Some pathogens have also become resistant to many commercially used antibiotics. Therefore, there is a need to develop new infection-fighting strategies from natural source to control pathogenic infections without cause any side effects. The cow urine has a best source of natural compounds with antimicrobial and antioxidant properties. In this present study, the cow urine was collected at different time intervals and the antibacterial activity of Photo activated, distillate and fresh raw cow urine were tested by agar well and pour plate method using the pathogenic microbes like pseudomonas auerogenisa, Bacillus subtilis, and Klebsiella pneumonia. The antioxidant activity of the Cow Urine and its fractions has been evaluated by Free Radical Scavenging Activity using DPPH assay method and Reducing Power Assay. In this result we found that the fresh and photo activated cow urine evidences for better antioxidant and antimicrobial activity by inhibiting Klebsiella pneumonia (31 and 27mm) compared to distillate. We conclude that the fresh and photo activated gomutra could be a potential source of natural antioxidant that would have greater importance as supportive therapy in slowing oxidative stress related degenerative diseases and also act as effective tool for inhibiting pathogenic infections.